Euphemism in IBerhamsyah Barbary's Verse 1001 Gurindam - Rosmawaty, Rosmawaty; Erlita, Yeni; Bahri, Syamsul (Randwick International of Social Science Journal, 2025)
The study on euphemism in IBerhamsyah Barbary’s 1001 Gurindam explores the use of refined language in traditional Malay poem. This study highlights the importance of language in conveying messages and ideas effectively while also avoiding impoliteness or offended feelings of others. The goal of the study is to examine the many kinds of euphemisms that are employed in the 1001 Gurindam verses and determine how they enhance the language's general elegance and civility. This study examined euphemism in IBerhamsyah Barbary's Verse 1001 Gurindam using a qualitative methodology. Taylor, Bogdan & Devault ( 2016 ) claimed that the descriptive qualitative approach is a research process that generates data from people's written or spoken words and observable behavior. The findings reveal that the most common types of euphemisms used in the 1001 Gurindam are Metaphors 39,65% , Jargon 22,41% and Figurative expressions 18,9%. These types of euphemisms are used to convey complex ideas and emotions more subtly and politely, making the language more refined and beautiful to hear. The study also highlights the use of other types of euphemisms, such as one-for-one substitutions 8,6% , colloquial expressions 6,8% and hyperbole 3,4%, which contribute to the overall refinement of the language. The study demonstrates that euphemism plays a significant role in refining the language used in traditional Malay poem, such as the 1001 Gurindam. The various types of euphemisms used in the verses contributing to the overall politeness and beauty of the language, making it more effective in conveying messages and ideas.